Pengaruh E-Service Quality, E-Trust, Dan Online Consumer Review Terhadap Keputusan Pembelian Pada E-Commerce Tokopedia - Pratama, Noveta; Darmawati, Darmawati; Parlina, Tika (Borneo Islamic Finance and Economics Journal, 2024)
Tokopedia is one of the largest e-commerce companies in Indonesia which has now succeeded and successfully exploited the great opportunities of using the internet so that Tokopedia currently has a good image to be the main factor for someone in making purchasing decisions online. The decision to purchase a product is a very important factor that companies must pay attention to in every trading activity because from a purchasing decision a transaction will occur. Several factors that influence purchasing decisions at Tokopedia in this research are E-Service Quality, E-Trust, and Online Consumer Reviews. The purpose of this research is to determine the influence of E- Service Quality, E-Trust, and Online Consumer Reviews on Purchase Decisions on Tokopedia E-Commerce. The method used in this research is casual associative quantitative research. The population in this study were Tokopedia users, Generation Z Muslims in East Kalimantan, totaling 1,025,006 people with an age range of 10-24 years for generation Z. The sample used was 100 Generation Z Muslims in East Kalimantan Tokopedia users using a sampling technique, namely purposive sampling. The data collection technique used was distributing questionnaires via Google Form with a Likert Scale measurement technique. The results of this research show that E-Service Quality, E-Trust, and Online Consumer Reviews partially have a significant influence on Purchase Decisions on Tokopedia E-Commerce. Likewise, simultaneously E-Service Quality, E-Trust, and Online Consumer Reviews, partially have a significant influence on Purchasing Decisions on Tokopedia E-Commerce. The R2 value is 0.846, which means that 84.6% of the Buying Decision variable in Tokopedia E-Commerce is influenced by the E-Service Quality, E-Trust and Online Consumer Review variables. Keywords: Purchase Decision, Tokopedia, E-Service Quality, E-Trust, Online Consumer Review, Generation Z